Math, asked by mahabubdarjee, 1 year ago

x= √( √ 5+1)/( √ 5-1) show that x^2-x-1=0

Answers

Answered by suhail2070
0

Answer:

{x}^{2}  - x  - 1 = 0

Step-by-step explanation:

x =  \sqrt{ \frac{ \sqrt{5} + 1 }{ \sqrt{5}  - 1} }  =  \sqrt{ \frac{ {( \sqrt{5} + 1 )}^{2} }{5 - 1} }  \\  \\  =  \sqrt{ \frac{ {( \sqrt{5} + 1 )}^{2} }{4} }  \\  \\  =  \frac{ \sqrt{5} + 1 }{2}  \\  \\ x =  \frac{ \sqrt{5}  + 1}{2}    \\  \\  {x}^{2}  =  \frac{ \sqrt{5} + 1 }{ \sqrt{5} - 1 }  =  \frac{ {( \sqrt{5} + 1 )}^{2} }{5 - 1}  =  \frac{ 5 + 1 + 2 \sqrt{5}}{4}  =  \frac{6 + 2 \sqrt{5} }{4}  =  \frac{3 +  \sqrt{5} }{2} \\  \\ therefore \:  \:  \:  \:  {x}^{2}  - x + 1 =  \frac{ \sqrt{5} + 3}{ 2 }  -  \frac{ \sqrt{5}  + 1}{2}  - 1 \\  \\  =  \frac{ \sqrt{5} + 3 -  \sqrt{5}   - 1 - 2}{2}  \\  \\  =  \frac{0}{2}  \\  \\  = 0 = rhs \\  \\ therefore \:  \:  \:  {x}^{2}  - x  - 1 = 0

Similar questions